PEMANFAATAN DIGITAL COMICS UNTUK MENINGKATKAN SCIENTIFIC LITERACY PESERTA DIDIK SEKOLAH DASAR - Shailia, Anjelita; Alif Luthvi Azizah; Nindy Profithasari; Ulwan Syafrudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the use of Digital Comics as a learning medium in Integrated Science (IPAS) on elementary students’ Scientific Literacy. The research employed a quasi-experimental method with a nonequivalent control group design involving 50 fifth-grade students of SD Negeri 2 Kota Gajah, divided into an experimental and a control class. The experimental class used digital comics, while the control class received conventional instruction. Data were collected through a valid and reliable Scientific Literacy test and analyzed using N-Gain. The results showed that the experimental class achieved higher improvement, with an average N-Gain of 0.48 (medium category), compared to the control class, which had 0.21 (low category) across all indicators. Thus, Digital Comics proved effective in enhancing Scientific Literacy in accordance with the Independent Curriculum. Keywords: digital comics, IPAS, scientific literacy,elementary school